2022
DOI: 10.5552/crojfe.2022.1639
|View full text |Cite
|
Sign up to set email alerts
|

Mental Workload, Occupational Fatigue and Musculoskeletal Disorders of Forestry Professionals

Abstract: Musculoskeletal disorders (MSD) comprise one of the most important occupational health issues in forestry professions. The purpose of the study was to examine the association among musculoskeletal disorders, antrhopometric and personal data, mental workload and occupational fatigue in forest professionals in northern Iran by means of the Nordic Musculoskeletal Questionnaire (NMQ), the National Aeronautics and Space Administration Task Load Index (NASA-TLX), and the Swedish Occupational Fatigue Inventory (SOFI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Manual work and tools are generally tied to measuring and managing operations in forestry [13,16,59,90] where workload and postural load were assessed. They are also involved in pre-harvesting and harvesting [15], e.g., postural load during manual cultivation and assistance with a wooden stick to help direct the felling; and wood extraction [15,48], e.g., MSD occurrence and workload while sorting small logs and manual loading, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual work and tools are generally tied to measuring and managing operations in forestry [13,16,59,90] where workload and postural load were assessed. They are also involved in pre-harvesting and harvesting [15], e.g., postural load during manual cultivation and assistance with a wooden stick to help direct the felling; and wood extraction [15,48], e.g., MSD occurrence and workload while sorting small logs and manual loading, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a higher slope gradient increased visual activity, indicating that the harvester operator experienced a heavier mental workload [47]. However, a study by Arman et al [48] on tree fellers, skidder drivers, and manual loaders recorded high scores for mental workload using a NASA-TLX questionnaire. Pajek et al [49] in their controlled study stated that there are significant differences in psychophysical load in regard to the clothing systems used by forest workers.…”
Section: Workloadmentioning
confidence: 97%
“…The data analysis aimed at the estimation of the relative heart rate (HRR) at work according to Equation (1) [ 37 , 38 ]: where HR work was the average heart rate during work, HR rest was the resting heart rate, and HR max was the maximum heart rate calculated for each subject by subtracting his age from 220. The validity of 220—age has been questioned for containing a degree of error [ 33 , 39 ]; however, it has been widely used in applied situations as is [ 37 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that tree felling and processing are the most demanding phases of harvesting trees [ 3 , 28 ]. It comes as no surprise that chainsaw operators suffer from high MSD prevalence [ 2 , 15 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological pressure can affect cognitive abilities (i.e., perception and problem solving) through affecting the workers' mental reserves [34,35] and result in lesser quality of forest operations, both in terms of the produced timber assortments and the environmental impacts of forest operations [36]. Similarly, stressful situations may create adverse working conditions, leading to increased frequencies of accidents and musculoskeletal disorders [37,38].…”
Section: Costmentioning
confidence: 99%